2016
DOI: 10.5114/dr.2016.61774
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde-related clinical symptoms reported by medical students during gross anatomy cadaver dissection

Abstract: Introduction. Formaldehyde is a noxious gas used as a tissue preservative of cadavers in autopsy rooms. Therefore, exposure to higher concentrations applies particularly to laboratory staff, anatomists and medical students. Prolonged exposure to formaldehyde is associated with clinical complications. Objective. To assess whether exposure to repeated inhalation of low concentrations of formaldehyde (FA) experienced during a gross anatomy course triggers subjective clinical symptoms in medical students. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Respiratory and GIT tract related symptoms were also observed among students where respiratory distress, cough and sore throat were at high prevalence. This finding was similar to that reported by previous studies [16,17,19]. Moreover, about half of students complained of low assimilation after they exposed to formaldehyde which might be due to the high prevalence of unusual tiredness, headache and dizziness documented in this study.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Respiratory and GIT tract related symptoms were also observed among students where respiratory distress, cough and sore throat were at high prevalence. This finding was similar to that reported by previous studies [16,17,19]. Moreover, about half of students complained of low assimilation after they exposed to formaldehyde which might be due to the high prevalence of unusual tiredness, headache and dizziness documented in this study.…”
supporting
confidence: 92%
“…Most of the students and staff members were interested in finding out about the effects of formaldehyde on their health, positively responded by returning the filled questionnaires to the researchers and were enthusiastic to see the results when the research is completed. Most students in this study had common undesirable effects related to the nose and eyes which are in agreement with the data reported by other studies [17,19,23]. Respiratory and GIT tract related symptoms were also observed among students where respiratory distress, cough and sore throat were at high prevalence.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Exposure levels in anatomy and pathology laboratories have always been extremely high, often exceeding the 2 ppm short-term exposure limit (STEL), primarily due to the evaporation of formaldehyde from the solution used for the preservation of tissues and specimens [9]. One study found that even when anatomy laboratories were not in use, minimum FA concentrations were still above 0.25 mg•m −3 , with a few extreme instances measuring between 13.01 and 20.94 mg•m −3 [10]. In a study conducted in pathological laboratories in Shanghai, the average FA concentration was 1.60 mg•m −3 , with the highest value of 5.84 mg•m −3 [11].…”
Section: Introductionmentioning
confidence: 99%